SDG Implementation at the Local Level: Lessons From Responses to the Coronavirus Crisis in Three Cities in the Global South - Mejía-Dugand, Santiago; Croese, Sylvia; Reddy, Shobha Ananda (Frontiers in Sustainable Cities, 2020)
A body of work is starting to emerge that seeks to build on the challenges and lessons of the current global coronavirus crisis for long term sustainability planning and development. This perspective article argues that central to such reflections should be an acknowledgement of the intense territorial impact of the crisis, especially in the places where most of the world’s population is increasingly living: cities. We review existing frameworks for SDG implementation in the cities of Bengaluru (India), Medellin (Colombia) and Cape Town (South Africa) and use this as the backdrop for an analysis of local responses to the pandemic. We build on this analysis to reflect on three main avenues for SDG implementation going forward: multi-level governance, the science-policy interface and citizen and society engagement. We argue that strengthening these structures and collaborations will be central to more sustainable, long-term inclusive and evidence-based decision-making processes and global policy implementation in cities in a post COVID-19 world.